SOLUSI IMMATURE PARENT DALAM AL- QUR’AN: TINJAUAN KH BISRI MUSTHAFA DALAM TAFSIR AL-IBRIZ - Rifqatul Husna; Siti Anisah (EGALITA, 2023)
Immature parents are a phenomenon in the form of emotional immaturity by parents who get toxic parents treatment in previous parenting which affects the next parenting pattern. What would happen if a parenting pattern was applied equally by custom and era. Meanwhile, the problems and circumstances of each era always develop and seem striking in terms of differences. The purpose of this study is to provide solutions to parents who are currently in a state of emotional immaturity due to the treatment of toxic parents in the previous care, so as not carry out the same parenting patterns to the next generation. By interpreting verses from the Qur’an and using this type of research with a qualitative approach, and assisted by primary and secondary literature sources which are then critically analyzed to form a framework of thought for researchers, which result in psychotherapy by performing the worship commanded by Allah SWT in the form of patience and prayer can train and build the soul to be stronger when it has experienced heavy buedens, deep pressures, and bad experiences.